Satiety effects of a dairy beverage fermented with propionic acid bacteria - Ruijschop, Rianne M.A.J.; Boelrijk, Alexandra E.M.; te Giffel, Meike C. (International dairy journal, 2008)
Organic acids, and in particular short-chain fatty acids, are reported to have satiety-inducing effects. The aim of this study was to investigate if a dairy beverage containing propionic acid obtained by fermentation induces more satiety and a greater decrease in food intake than a non-fermented dairy product. In a within-subjects repeated-measures design, 43 young, healthy, normal-weight women consumed 150 mL, 1.0 MJ each of the fermented dairy beverage, a non-fermented dairy beverage (placebo) and a non-fermented dairy beverage with addition of 0.6% calcium propionate (positive control). Actual food intake of cold pasta salad was measured 25 min after finishing each preload. Subjects felt significantly fuller ( F = 4.21; P = 0.02), were less hungry ( F = 4.49; P = 0.004) and had less desire to eat ( F = 5.34; P = 0.006) after consumption of the fermented dairy beverage and positive control compared with the placebo. However, there was no effect on ad libitum food consumption.